Disentangling entanglements in biopolymer solutions - Philipp Lang (Nature Portfolio, 2018)
Reptation theory has been widely adopted to describe the dynamics of entangled polymer solution, whereby a polymer follows the curvilinear Brownian motion along a tube. Here, the authors challenge this theory by showing long-time dynamics of semi-flexible polymers modulated by topological constraints.